SPINACH (Amaranthus tricolor L.) GROWTH USING ORGANIC FERTILIZER FROM Trichoderma harzianum DECOMPOSITION RESULT - Anhar, Azwir; Advinda, Linda; Mulyadi, Rival; Irdawati, Irdawati; Leilani, Irma (IAIN Batusangkar, 2017)
Long term period of using fertilizers is not beneficial for soil fertility due to decreasing soil organic matter content. Otherwise, the source of organic matter widely available as waste in the environment are not used optimally because the naturally decomposition quite long time. This problem can be overcome by utilizing various types of microbes, such as Trichoderma. This research conducted to determine the effect of organic fertilizer from the decomposition result of T. harzianum in enhancing growth of spinach plant. This study used a completely randomized design (CRD) with 6 treatments and 4 replications. The treatments were doses variation of decomposition of organic material; 0 g, 15 g, 30 g, 45 g, 60 g and 75 g. Data were analyzed with ANOVA and continued with Duncan New Multiple Range Test (DNMRT). The results showed that the application doses of organic fertilizer from decomposition result influences height, number of leaves, leaf area, fresh weight and dry weight of spinach plants. Optimal dose for all growth is 45 grams/polybag.